BioCurve Analyzer: a web-based shiny app for analyzing biological response curves - Zenan Xing; James Eckhardt; Aditya S. Vaidya; Sean R. Cutler (Plant Methods)
Abstract Background Dose–response and time-to-event data are common in enzymology, pharmacology, and agronomy studies. Diverse biological response curves can be generated from such data. The features of these curves can be elucidated through parameters such as ED50 (the effective dose that gives 50% of the maximum response) and T50 (the time required to reach 50% of the maximum response). Properly estimating these parameters is crucial for inferring the potency of compounds or the relative timings of biological processes. Results We present an open-source Shiny application, BioCurve Analyzer, that simplifies the process of inferring ED50 and T50 parameters from response curves exhibiting various patterns, including classic monotonic sigmoidal curves and more complicated biphasic curves. BioCurve Analyzer provides access to several packages and commonly used models for characterizing response patterns, assists users in identifying the models that best describe their data, and includes options for inferring ED50 values on both sides of biphasic curves. BioCurve Analyzer also facilitates the visualization of response patterns and allows users to customize their final graphical representation to deliver publication-quality graphs of the data. Conclusion BioCurve Analyzer integrates multiple R packages in an easy-to-use web-based interface to facilitate dose–response and time-to-event analyses.